Pengendalian Diaphorina citri (Vektor Penyakit CVPD) dengan Metarrhizium anisopliae - Kardi Raharjo; Susamto Somowiyarjo; F. X. Wagiman (Jurnal Perlindungan Tanaman Indonesia, 2000)
CVPD is transmitted by Diaphorina citri. Measures to control D. citri by using biological controlling agents have opportunity to reduce insecticide application. The objectives of the research are: to measure effectiveness of Metarrhiziurn anisopliae (Metch.) Sorok. in controlling D. citri, effect fructose and time application namely before and after insect infestation. The first phase of the research phase has been conducted in Temanggung, Completely Randomize Design (CRD) factorial with three time replication. Factor I: sterile water without fructose, concentration 10^6 conidia/ml without fructose, concentration 10^8 conidia/ml without fructose, concentration 10^10 conidia/ml: without fructose, sterile water + fructose 5 mg/ml, concentration 10^6 conidia/ml without fructose 5 mg/ml, concentration 10^8 conidia/ml + fructose (fungi application before insect infestation) and W1 (fungi application after insect infestation). Research phase II was carried out with the best treatment combination compare with control treatment in Temanggung and Bantul. The results of experiment showed that the initial die of D. citri caused by M. anisopliae infection are on 4-6 days after application. The application of M. anisopliae at concentration 10^10 conidia/ml without fructose, applied after insect infestation was most effective. The application after insect infestation was more effective compare with application before insect infestation especially on 4 days after application, but on 35th days after application there was no significant difference. Fructose has no effect to mortality of D. citri.